High Performance Human Resource and Corporate Entrepreneurship: - Gilani, H.R. (Al-Qanṭara, 2022)
Abstract: The purpose of this paper aims to clarify the relationship between high performance human resource practices and corporate entrepreneurship, and tries to demonstrate the mediator role of citizenship behavior and procedural justice in this relationship. In this study sample included 93 small- to-medium-sized enterprises in Guilan province. It is argued here that previous studies have emphasized the positive impact of human resource management practices. In contrast to prior research, this paper shows that high performance human resources practices is positively related to corporate entrepreneurship and this relationship is mediated by the organizational behavior and procedure justice. One limitation of findings is that, training and reward are not positive related to corporate entrepreneurship, but with mediating role of organizational citizenship behavior and procedure justice the relationship was significant.